A new turtle from the La Colonia Formation (Campanian–Maastrichtian), Patagonia, Argentina, with remarks on the evolution of the vertebral column in turtles - Sterli, Juliana (2011)
Patagoniaemys gasparinae gen. et sp. nov. is a new stem-turtle found in Central Patagonia, Chubut Province, Argentina in outcrops of the La Colonia Formation (Campanian–Maastrichtian). This is a turtle of relatively large size (carapace length approximately 70 cm) and the preserved remains of the holotype consist of skull fragments and several postcranial elements including a nearly complete vertebral column. A phylogenetic analysis shows Patagoniaemys gasparinae gen. et sp. nov. forming a monophyletic group with Otwayemys cunicularius and Mongolochelys efremovi, as a sister group to Meiolaniidae. A comprehensive review suggests that formed cervical vertebrae appeared independently several times during turtle evolution: in the clade that includes Patagoniaemys gasparinae gen. et sp. nov. and Meiolaniidae, in some baenids, in the total group Pleurodira and in crown group Cryptodira. Likewise, formed caudal vertebrae appeared several times in turtle evolution.